Towards plasma cleaning of ITER first mirrors. (8th May 2015) - Moser, L.; Marot, L.; Eren, B.; Steiner, R.; Mathys, D.; Leipold, F.; Reichle, R.; Meyer, E.
Abstract: To avoid reflectivity losses in ITER's optical diagnostic systems, on-site cleaning of metallic first mirrors via plasma sputtering is foreseen to remove deposit build-ups migrating from the main wall. In this work, the influence of aluminium and tungsten deposits on the reflectivity of molybdenum mirrors as well as the possibility to clean them with plasma exposure is investigated. Porous ITER-like deposits are grown to mimic the edge conditions expected in ITER, and a severe degradation in the specular reflectivity is observed as these deposits build up on the mirror surface. In addition, dense oxide films are produced for comparisons with porous films. The composition, morphology and crystal structure of several films were characterized by means of scanning electron microscopy, x-ray photoelectron spectroscopy, x-ray diffraction and secondary ion mass spectrometry. The cleaning of the deposits and the restoration of the mirrors' optical properties are possible either with a Kaufman source or radio frequency directly applied to the mirror (or radio frequency plasma generated directly around the mirror surface). Accelerating ions of an external plasma source through a direct current applied onto the mirror does not remove deposits composed of oxides. A possible implementation of plasma cleaning in ITER is addressed.